Factors related to the choice of warfarin for treating newly diagnosed nonvalvular atrial fibrillation are associated with safety outcomes during anticoagulation: A new‐user, active‐comparator, retrospective cohort study - Yoshiko Takagi; Shinichiro Ueda (Journal of Arrhythmia)
Abstract Background Direct oral anticoagulants (DOACs) are preferred for stroke prevention in nonvalvular atrial fibrillation (NVAF); however, warfarin is still used. This study examined why physicians may choose warfarin over DOACs and the associated safety outcomes in patients with NVAF. Methods We conducted a new‐user, active‐comparator cohort study in newly diagnosed patients with NVAF to assess safety outcomes after the introduction of DOACs in Japan. Results The median observation period was 1120 days; 1428 patients started anticoagulation therapy with warfarin and 1551 with DOACs. Warfarin was chosen for patients with lower creatinine clearance and left ventricular ejection fractions and those using aspirin and verapamil. The unadjusted risk of major bleeding was considerably higher in the warfarin group but was nonsignificant after adjusting for variables associated with the choice of warfarin, in addition to age and sex. The risk of death was higher in the warfarin group, even after adjustments for relevant variables. However, high‐risk subgroups, including those with older ages and multiple comorbidities, such as renal impairment, for whom warfarin was more likely to be selected, had severely compromised prognoses with either anticoagulant. The risk of stroke/systemic embolism was not significantly different between the two groups. Conclusions Warfarin is often chosen for older patients with multiple comorbidities characterized by reduced renal function, which is associated with a higher risk of major bleeding and mortality. These high‐risk patients seem to have a poor prognosis regardless of the type of anticoagulant used. Thus, safe anticoagulant therapy remains a challenge for such patients.